Plastics in human diets: development and evaluation of the 24-h Dietary Recall — Plastic Exposure and the Dietary Plastics Score - Harray, Amelia; Herrmann, Susan; Papendorf, Hannah; Miller, Claire; Vermeersch, Andrea; Smith, Tony; Lucas, Michaela (Frontiers in Nutrition, 2024)
Background: Humans are commonly exposed to plastic through their dietary intake and food consumption patterns. Plastic-associated chemicals (PAC), such as bisphenols and phthalates, are recognised as endocrine-disrupting and are associated with increased risk of cardiovascular disease and metabolic syndrome. However, accurate methods to assess dietary exposure to plastic products and PAC are inadequate, limiting interrogation of health impacts. Aim: To develop a tool that captures complete dietary exposure to plastics and establish a diet quality score to measure adherence to a low plastic dietary pattern. Methods: We developed the 24-hour Diet Recall -Plastic Exposure (24DR-PE) and administered it to healthy adults (n=422). This computer-assisted, interviewer-administered tool systematically collects data on food volumes and types, packaging materials, storage, processing, cooking, and consumption methods to assess a food's exposure to plastic. Specifically, the 24DR-PE incorporates predefined criteria for identifying high-risk practices and food characteristics, such as individually packaged items or those microwaved in plastic, enabling the assignment of scores based on a theoretically derived Dietary Plastics Scoring Matrix. Conclusion: The 24DR-PE is the first tool specifically designed to capture detailed data on dietary exposures to plastic products. The next step is to validate the score using laboratory results of urine samples we collected contemporaneous to the dietary information. Once validated, the tool has potential for widespread distribution making it valuable for population monitoring, intervention guidance, and future research investigating the interplay between plastics, diet, and human health.